Sistem Informasi Pariwisata Kabupaten Pemalang Selatan yang Berbasis Web - Nailun Ni’mah, Afina (CV RIFAINSTITUT, 2021)
The web-based South Pemalang Regency tourism information system is used as a tool in delivering information on tourist and cultural areas in Pemalang Regency to people who want to know tourist areas in Pemalang Regency. The web-based Pemalang Regency tourism information system is one form of regional tourism promotion in Pemalang Regency, in order to attract tourists to visit Pemalang Regency. The research methods used include direct observation, interviews with related parties, and literature studies related to the issues raised. The application development methodology that the author uses is the waterfall model. The programming language used is Sublime Text using mysql as the database. This research is useful as a medium of information and promotion of tourism potential in Pemalang Regency, so that people will be more familiar with regional tourism places in Pemalang Regency. The more tourists who visit, the income of the area and the surrounding community will increase.